The Rise of Symptoms of Digital Authoritarianism: Lesson from Indonesia - Sihidi, Iradhad Taqwa (Internasional Journal of Politics and Public Policy, 2025)
This paper specifically looks at the practice of repression in Indonesia's digital space, which strongly contributes to the phenomenon of digital authoritarianism in 2022. This study uses qualitative analysis with a literature study approach to clarify this assumption. The primary data from the 2021 Safenet report on digital rights in Indonesia is reinforced by relevant journals, books, and other credible online sources. This research shows that Indonesia is getting closer to the symptoms of Digital Authoritarianism with six indicator, namely the increasing criminalization experienced by citizens, journalists, and activists using the Electronic Information and Transactions Law (ITE Law), internet connection termination, online or online censorship in the form of closing certain sites without going through previous legal processes, the increasingly widespread government supervision of citizens' activities on the internet especially after the establishment of cyber police and the rise of digital thuggery on social media.